Implementing Hybrid Cloud with Azure Arc - Malik, Amit; Kaur, Daman; N, Raja (Packt Publishing, 2021)
Accelerate hybrid cloud innovation using Azure Arc with the help of real-world scenarios and examples Key Features Get to grips with setting up and working with Azure Arc Harness the power of Azure Arc and its integration with cutting-edge technologies such as Kubernetes and PaaS data services Manage, govern, and monitor your on-premises servers and applications with Azure Book Description With all the options available for deploying infrastructure on multi-cloud platforms and on-premises comes the complexity of managing it, which is adeptly handled by Azure Arc. This book will show you how you can manage environments across platforms without having to migrate workloads from on-premises or multi-cloud to Azure every time. Implementing Hybrid Cloud with Azure Arc starts with an introduction to Azure Arc and hybrid cloud computing, covering use cases and various supported topologies. You'll learn to set up Windows and Linux servers as Arc-enabled machines and get to grips with deploying applications on Kubernetes clusters with Azure Arc and GitOps. The book then demonstrates how to onboard an on-premises SQL Server infrastructure as an Arc-enabled SQL Server and deploy and manage a hyperscale PostgreSQL infrastructure on-premises through Azure Arc. Along with deployment, the book also covers security, backup, migration, and data distribution aspects. Finally, it shows you how to deploy and manage Azure's data services on your own private cloud and explore multi-cloud solutions with Azure Arc. By the end of this book, you'll have a firm understanding of Azure Arc and how it interacts with various cutting-edge technologies such as Kubernetes and PaaS data services. What you will learn Set up a fully functioning Azure Arc-managed environment Explore products and services from Azure that will help you to leverage Azure Arc Understand the new vision of working with on-premises infrastructure Deploy Azure's PaaS data services on-premises or on other cloud platforms Discover and learn about the technologies required to design a hybrid and multi-cloud strategy Implement best practices to govern your IT infrastructure in a scalable model Who this book is for This book is for Cloud IT professionals (Azure and/or AWS), system administrators, database administrators (DBAs), and architects looking to gain clarity about how Azure Arc works and how it can help them achieve business value. Anyone with basic Azure knowledge will benefit from this book.